Hepatoprotective Effect of Honey and Black Cumin Combination Against Soft Drink-Induced Rattus norvegicus Liver Based on Histopathological Features - Annisa Banowati; Fitria Diniah Janah Sayekti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Carbonated soft drinks are drinks that can cause damage to the liver if consumed excessively. The combination of honey and black cumin as an antioxidant agent has hepatoprotective and antioxidant effects with a capacity of 3-4 times compared to honey or black cumin seeds alone. The aim of this research was to determine the effect on macroscopic and microscopic observations of the liver of Rattus norvegicus given a combination of honey and black cumin in graded doses, namely concentrations of 25%, 50% and 75% after being induced by soft drinks and the damage that occurred when given in doses and the specified time. This research was carried out experimentally at the Cytohistotechnology Laboratory Sekolah Tinggi Ilmu Kesehatan Nasional. The research was divided into 6 groups, namely 3 control groups and 3 treatment groups. The results of macroscopic observations showed differences in colour, size, fatty and similarities in liver texture. The results of microscopic observations showed normal cells and damage such as hydropic degeneration, parenchymatous degeneration, pyknosis necrosis, karyorrhexic necrosis, and karyolysis necrosis. The results of the test using One Way ANOVA and followed by Post Hoc Duncan can be concluded that giving a combination of honey and 75% black cumin as much as 2 mL/200 gr weight of rats can have a protective effect on macroscopic and microscopic examination of the liver of Rattus norvegicus after being induced by soft drinks.